2022
DOI: 10.32098/mltj.04.2022.17
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization Exercises versus Flexi-Bar Exercises in Chronic Non-Specific Low Back Pain: Pain, Disability, Back Muscles Endurance. A Randomized Controlled Trial

Abstract: Background. Low back pain (LBP) is one of the most prevalent and costly musculoskeletal problems. Impaired neuromuscular control and reduced use of the dorsal and abdominal muscles lead to instability in the spine and subsequent injury. Recently, vibration therapy has been proposed as an alternative method for LBP rehabilitation. Flexi-bar is a vibratory tool. When it is shaken, the core muscles are automatically activated to control the trunk against oscillatory forces created by the Flexi-bar. This study aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…One study was an excellent quality study, five studies were good quality studies, and two studies were fair quality studies. Ten studies, however, concluded that CST had no advantage over other exercise therapies in improving pain (Ahmadizadeh et al, 2020;Alp et al, 2014;Amiri et al, 2022;Areeudomwong & Buttagat, 2019;Bae et al, 2018;Franca et al, 2010;Nabavi et al, 2018;Salamat et al, 2017;Ulger et al, 2023;Wang et al, 2022). Three of the studies were excellent quality studies, six were good quality studies, and one was a fair quality study.…”
Section: Articles On Cst Improving Low Back Pain In Adultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study was an excellent quality study, five studies were good quality studies, and two studies were fair quality studies. Ten studies, however, concluded that CST had no advantage over other exercise therapies in improving pain (Ahmadizadeh et al, 2020;Alp et al, 2014;Amiri et al, 2022;Areeudomwong & Buttagat, 2019;Bae et al, 2018;Franca et al, 2010;Nabavi et al, 2018;Salamat et al, 2017;Ulger et al, 2023;Wang et al, 2022). Three of the studies were excellent quality studies, six were good quality studies, and one was a fair quality study.…”
Section: Articles On Cst Improving Low Back Pain In Adultsmentioning
confidence: 99%
“…In terms of improving trunk muscular endurance, two good-quality studies showed that CST was more effective than other exercise therapies (Alp et al, 2014;Salik Sengul et al, 2021). However, two good-quality studies showed that CST was less effective than Flexibar exercise, walking exercise, and stabilization with walking (Amiri et al, 2022;Suh et al, 2019).…”
Section: Articles On Cst Improving Trunk Muscular Endurance In Adultsmentioning
confidence: 99%